1999
DOI: 10.1094/cchem.1999.76.5.743
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Single Substitution of Glutenin or Gliadin Proteins on Flour Quality of Alpha 16, a Canada Prairie Spring Wheat Breeders' Line

Abstract: Cereal Chem. 76(5):743-747The effect of genetic variation in the glutenin and gliadin protein alleles of Alpha 16, a Canada Prairie Spring (CPS) wheat line, on the dough mixing, bread, and noodle quality properties were evaluated. The presence of a gliadin component (BGGL) and the low molecular weight glutenin subunit (LMW-GS) 45 found in the selection Biggar BSR were associated with significant increases in dough strength characteristics. The results of the study showed that gliadins, LMW-GS, and high molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 11 publications
1
16
0
Order By: Relevance
“…There are several reports about the interaction between HMW-GS and LMW-GS on the effect on the parameters of flour quality (Brites and Carrillo 2001, Flaete and Uhlen 2003, Nieto-Taladris et al 1994, Wesley et al 1999, Wesley et al 2001. Gupta et al (1994) reported that a combination of Glu-D1d/Glu-B3b exerted an additive effect, increasing the maximum resistance in the extensigraph test.…”
Section: Discussionmentioning
confidence: 99%
“…There are several reports about the interaction between HMW-GS and LMW-GS on the effect on the parameters of flour quality (Brites and Carrillo 2001, Flaete and Uhlen 2003, Nieto-Taladris et al 1994, Wesley et al 1999, Wesley et al 2001. Gupta et al (1994) reported that a combination of Glu-D1d/Glu-B3b exerted an additive effect, increasing the maximum resistance in the extensigraph test.…”
Section: Discussionmentioning
confidence: 99%
“…Characterisation of specific alleles at the Glu-3 loci has been conducted with respect to their effect on dough resistance and extensibility recently (Wesley et al 1999;Brites and Carrillo 2001;Luo et al 2001;Wesley et al 2001). Several Glu-3 alleles have been ranked in terms of their dough quality effects (Gupta and Shepherd 1988;Gupta et al 1989Gupta et al , 1990aGupta et al , 1990bGupta et al , 1991Metakovsky et al 1990).…”
Section: Introductionmentioning
confidence: 99%
“…HMWG subunits 17ϩ18 were not significantly different from subunits 7ϩ9 or 7ϩ8 with a background of subunits 5ϩ10 on bread-making quality, as found by Wesley et al (1999). Subunits 17ϩ18 had higher values of functional properties than subunits 7ϩ9 with a background of subunits 2.2ϩ12.…”
Section: Discussionmentioning
confidence: 62%
“…It has also been reported that there has been an interaction between the Glu-1 and Glu-3 alleles (Khelifi & Branlard 1992, Gupta et al, 1994 and that some subunits at the Glu-3 locus had a strong effect on the functional properties (Wesley et al, 1999. We would like to go on to research relationships between Glu-1 and Glu-3.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation